5G-assisted telementored surgery. Issue 12 (4th September 2019) - Lacy, A M; Bravo, R; Otero-Piñeiro, A M; Pena, R; De Lacy, F B; Menchaca, R; Balibrea, J M
Graphical Abstract: Safe and effective implementation of remote surgery and telementoring can have significant limitations. Fifth-generation (5G) wireless networks could be useful in overcoming these drawbacks. As a proof of concept, the authors present technical and clinical details of two procedures assisted by telementoring using 5G that were also broadcast live. Secure remote access advice